MENOPAUSE AND CARDIOVASCULAR RISK - D. A. Anichkov; N. A. Shostak; A. D. Zhuravleva (Столичная издательская компания, 2015)
A role of menopause as a cardiovascular risk factor is reviewed. Menopause influence on the cardiovascular system may be mediated by body fat re-allocation, metabolic, hemodynamic and pro-inflammatory changes. Besides, estrogen deprivation has a direct effect on the arterial wall. Lifestyle modification, lipid-lowering and antihypertensive treatment should be considered for cardiovascular risk reduction in postmenopausal women.